Cognitive-matrix analysis of research on primary health care development in the Russian Federation for the period from 2012 to 2022 - S. A. Orlov; R. N. Shepel; D. V. Voshev; D. O. Savchenko; D. A. Gellekh; А. B. Gorlov; K. S. Mezhidov; M. V. Turlay; A. V. Sentsova; L. M. Zhamalov; A. V. Kontsevaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The distribution of publications posted in the Elibrary for the period from January 1, 2012 to December 31, 2022, in the structure of a cognitive matrix of taxonomic characteristics for the analysis and assessment of primary health care in the Russian Federation made it possible to establish areas of scientific interest and identify gaps in specific areas and indicators characterizing its current and future development.Aim. To distribute scientific publications according to the relevant segments of the cognitive matrix of taxonomic characteristics for the analysis and assessment of primary health care in the Russian Federation.Material and methods. A database of 41824 publications was used, for which a triple review was carried out with the involvement of 9 experts selected according to appropriate criteria for level of education, work experience in the healthcare system, and academic credentials. At the first two stages, publications not related to primary health care, as well as duplicate publications, were excluded. At the final stage of reviewing, a selective analysis of publications was carried out, assessing the correctness of their distribution into the corresponding taxa of the cognitive matrix, followed by adjustment (if necessary).Results. A cognitive matrix of taxonomic characteristics has been generated for the analysis and assessment of primary health care in the Russian Federation, containing 30339 publications distributed across relevant domains, subdomains and primary health care indicators. The matrix is also presented in a heat map format, allowing an assessment of the most studied taxa of primary health care, as well as highlighting those areas in primary health care in which more research should be carried out to provide a basis and methodology for making informed decisions on its development.Conclusion. Systematized and ordered publications can serve as a basis for a wide range of users in the preparation of systematic reviews and other publications on specific domains, subdomains, primary health care indicators and universal health coverage principles. This study has shown the high efficiency of the cognitive matrix of taxonomic characteristics as a unified tool for aggregation or decomposition of features characterizing the development of primary health care in the Russian Federation.